Plasmoid statistics in relativistic magnetic reconnection - Petropoulou, M.; Christie, I. M.; Sironi, L.; Giannios, D. (OUP, 2018)
Plasmoids, overdense blobs of plasma containing magnetic fields and high-energy particles, are a self-consistent outcome of the reconnection process in the relativistic regime. Recent two-dimensional particle-in-cell (PIC) simulations have shown that plasmoids can undergo a variety of processes (e.g. mergers, bulk acceleration, growth, and advection) within the reconnection layer. We developed a Monte Carlo code, benchmarked with the recent PIC simulations, to examine the effects of these processes on the steady-state size and momentum distributions of the plasmoid chain. The differential plasmoid size distribution is shown to be a power law, ranging from a few plasma skin depths to ∼0.1 of the reconnection layer's length. The power-law slope is shown to be linearly dependent upon the ratio of the plasmoid acceleration and growth rates, which slightly decreases with increasing plasma magnetization. We perform a detailed comparison of our results with those of recent PIC simulations and briefly discuss the astrophysical implications of our findings through the representative case of flaring events from blazar jets.
Keywords: Accretion; accretion discs; Astrophysics - High Energy Astrophysical Phenomena; galaxies: jets; gamma-ray burst: general; magnetic reconnection